Microevolutionary changes of commercial Saccharomyces cerevisiae strains recovered from vineyard environments identified by comparative genome hybridization on array - Duarte, Ricardo Franco (2011)
The use of commercial Saccharomyces cerevisiae wine yeast strains as fermentation starters has been extensively generalised over the past two decades. These strains are used by wineries every harvest time in large quantities. Within our previous work we showed that such strains are disseminated from the winery [1] and their permanence in nature induced genetic changes that were not found among a control group of isolates that derived from clonal expansion of the commercial “mother” strain [2]. The objective of the present study was to evaluate genome variations among four isolates of the commercial strain S. cerevisiae Zymaflore VL1 that were re-isolated from vineyards surrounding the wineries where this strain was applied, in comparison to the commercial “mother” strain, by the use of comparative genome hybridization on array. These approaches were carried out as described [3]. Data analysis showed genetic differences among the recovered isolates in comparison with the “mother” strain. Amplification (between 1 and 2 fold changes) of 14 genes were detected, related with mitosis (SHE1) or meiosis (HFM1), lysine biosynthesis (LYS14), galactose (GAL1) and asparagine catabolism (ASP3-2). ASP3-2 amplification is in agreement with the previously shown increased expression during nitrogen starvation. This might occur as an adaptation to natural environments with poor yeast-utilizable nitrogen sources. Eight Ty elements were also amplified, whereas each of the recovered strains had a unique pattern of amplifications. Phenotypic screening was performed considering 28 physiological tests. Seven phenotypic traits distinguished recovered strains from the “mother” strain which was unable to grow at 18ºC, but evidenced some growth in the presence of CuSO4 5mM and SDS 0.01%. Variable growth patterns were found for NaCl 1.5M, KHSO3 (300 mg/l) and wine supplemented with glucose (0.5% and 1% w/v). We hypothesize that the transition from nutrient-rich musts to nutritionally scarce natural environments induces adaptive responses and microevolutionary changes promoted by Ty elements. These changes (and possibly others as well) may contribute to intra-strain phenotypic variability.